Rating assessment of scientific and pedagogical workers: theoretical and methodical aspects within a market approach - Dzoba, O. H. (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2019)
The article investigates the theoretical and methodological principles of scientific and pedagogical workers rating assessment in higher educational institutions (HEI). According to the results of broad literature analysis, rating systems formation peculiarities of scientific and pedagogical university workers were determined. Further development of approaches to specification and detailing of the essence, functions, purposes and tasks of rating assessment, formation of principles, requirements and criteria, justification and rating models selection, harmonization of theoretical concepts with the practice of applying procedures for rating assessment in the HEI is substantiated. Research novelty is to elaborate on the essence and functions of scientific and pedagogical workers rating assessment system being considered as a multidimensional information system, which in turn is the subsystem of a more general management system. Scientific and pedagogical workers rating assessment system involves continuous observation, measurement and controlled object conditions evaluation, operational management decisions adoption, ensures the implementation, verification and review of management objectives, promotes educational and scientific standardization processes, provides ongoing regulation and forecasts further development. Rating assessment system is inextricably linked with professional activities monitoring of scientific and pedagogical workers in higher educational institutions and performs similar functions, such as informational, management, systematic, predictive, activating, analytical, qualimetric, corrective, diagnostic and formative ones. An important element of the scientific novelty studies is the feasibility justification of using a market approach based on marketing, social and ethical concepts marketing in formulating the goals, objectives and rating systems constructing principles for scientific and pedagogical workers. It is established that the most relevant principles in scientific and pedagogical workers rating systems formation are the principles of integrity with the general management system, dynamism and adaptability, orientation towards the needs of educational and scientific services consumers. Prospects for further research are related to the theoretical foundations development and methodology for building marketing complexes of educational and scientific services aimed at maximizing the consumers and society needs, which will be attained through more efficient management of human resource potential based on the use of rating models.